Pengaruh Reward Dan Punisment Terhadap Kinerja Karyawan Pada Toko Sembako - Zahra Aji Muqodimatul Janah; Enjang Suherman (Jurnal Ekonomi dan Bisnis Digital, 2024)
Finding out how rewards and penalties impact worker performance in a grocery shop was the aim of this study. The performance of the employees is the dependent variable in this research (Y). While punishment (X2) and reward (X1) are the independent variables. The 68 workers of grocery stores made up the population used in this study. Descriptive and quantitative research methodologies are employed. The findings demonstrated that, when it came to staff performance at a grocery shop, rewards had a substantial positive impact and penalties had a big negative one.